The effects of exercise at different temperatures on cognitive function: A systematic review. (May 2021) - Donnan, Kate; Williams, Emily L.; Morris, Jade L.; Stanger, Nicholas
Abstract: To date, no review has focused specifically on the potential modulating role of environmental temperature on the effects of exercise on cognitive function. Despite this, a range of occupations and performance contexts exist (e.g., military personnel, emergency services, sport) where the maintenance of cognitive function in environmentally challenging environments is crucial. Therefore, this systematic review aimed to evaluate the experimental research investigating how manipulating environmental temperature influenced the effects of acute bouts exercise on cognitive functioning from pre-to-post exercise, or during exercise. Studies to be included were assessed by two authors reviewing title, abstract, and then full-text. From the searches conducted, twenty articles were identified which met the inclusion criteria. For the purpose of this review, exercise involved in each study was categorised into low, moderate, and vigorous dosages (dependent on intensity and duration). The results indicate that moderate dosages of exercise help stimulate improved cognitive performance from pre-to-post exercise in temperate conditions, where cold exposure appears to blunt these effects. In addition, hot environments led to cognitive decrements during and post exercise which were often identified in studies that implemented prolonged moderate or vigorous exercise protocols. Therefore, suggesting a combination of heightened physiological strain from increased dose of exercise, alongside heat exposure, can be detrimental to optimal cognitive functioning, whereby executive functioning tasks appeared to be most affected. The findings from this systematic review highlight the potential modulating role of environmental temperature on the effects of exercise on cognitive function. Thus, highlighting the importance of considering the role of environmental temperature for individuals either exercising to elicit desired cognitive benefits or for those involved in physically demanding occupations or performance domains. Highlights: Acute moderate exercise benefits cognition post-exercise in temperate environments. Cold exposure appears to blunt cognitive benefits of acute moderate exercise. Prolonged moderate or vigorous exercise in the heat can cause cognitive decrements.